Temporal variations of metals and trace elements in tuna spines from the canary islands from 1990s to 2000s - Eunice Vásquez-Domínguez; Enrique Lozano-Bilbao; Pedro J. Pascual Alayón; Arturo Hardisson; Iván Casañas Machin; Soraya Paz; Dailos Gonález-Weller; Carmen Rubio; Ángel J. Gutiérrez (Scientific Reports)
Abstract Tuna, due to their position in the food web, serve as excellent biomonitors for assessing the health of marine ecosystems. Analyzing their organs and tissues provides valuable insight into element concentrations, as tuna possess the capacity to bioaccumulate pollutants. In the present study, 12 trace elements and metals (Al, B, Cd, Co, Cr, Cu, Fe, Li, Mo, Ni, Pb, Zn) were analyzed in dorsal fin spines samples of four tuna species: Katsuwonus pelamis, Thunnus albacares, Thunnus obesus and Thunnus thynnus from individuals captured in the surrounding waters of the Canary Islands, between 1990 and 2007. To analyze the data, descriptive statistics and one-way and two-way PERMANOVAs were carried out, with species factor and decade-species as factors, respectively. The highest concentrations were recorded for the elements: Al, Fe, B and Zn, with greater significant differences between species in the concentrations of Cu, and in both decades, in Fe, Pb and Zn. The comparison of the concentrations of elements between decades showed a decrease in them, from the 90s to the 2000s. There is no similar information on the metal content in spines for these species, providing relevant information, which may be of interest to future studies.